The Piston Ring-Cylinder Bore Interface Leakage of Bent-Axis Piston Pumps Based on Elastohydrodynamic Lubrication and Rotation Speed - Lvjun Qing; Lichen Gu; Yan Wang; Wei Xue; Zhufeng Lei (Shock and Vibration)
The bent-axis piston pump is the core component of electrohydrostatic actuators (EHA) in aerospace applications, and its wear of key friction interfaces is greatly related to the healthy operation of pumps. The leakage of the piston ring-cylinder bore interface (PRCB), as the important part of the return oil flow of the pump house that commonly assesses the wear of key friction interfaces in piston pumps, is changed with the rotation speed. Thus, the wear of key friction interfaces is usually inaccurate by using the leakage of PRCB. In order to obtain the relationship between the PRCB leakage and the rotation speed, an elastohydrodynamic lubrication model is proposed. First, the proposed model includes a minimum film thickness model of PRCB to analyze the dynamic change of oil film of PRCB when subject to the elastohydrodynamic lubrication. After that, a mathematical model of PRCB is induced by combining the minimum film thickness model with the flow equation, which helps produce the effects of the oil film on the leakage of PRCB. The proposed model is verified by numerical simulation and experiment. The results show that the leakage of PRCB has a negative effect on the return oil flow of the pump case in the range of rotation speed of 700–1300 r/min and discharge pressure of 10–20 MPa. Furthermore, the leakage of PRCB is proportional to the rotation speed, but the return oil flow of the pump case is decreased. The effects of rotation speed are enhanced under the high discharge pressure conditions.